Binary Mixtures of ZnO/TiO2 for Solar Heterogeneous Photocatalysis of Non-Purgeable Organic Carbon in Landfill Leachate (Research, Society and Development, 2022)
Landfill leachate is a global problem that has attracted considerable attention from researchers in different areas. It is crucial to develop optimized treatment strategies for landfill leachate, given the need to minimize or eliminate negative environmental impacts resulting from the inadequate disposal of solid waste, as determined by legislation. Landfill leachate is primarily composed of humic substances, which may associate with other toxic molecules and are recalcitrant to the conventional treatments used in Brazil. This study assessed the photocatalytic degradation of carbonaceous materials in leachate collected from the Cachoeira Paulista municipal landfill, São Paulo State, Brazil. Sunlight was used as energy source without additional light inputs. Experiments were carried out in a thin-film fixed-bed reactor, using metal plates coated with paints formulated for this purpose. Paints had a low additives loading, including that of photocatalysts. We investigated the photocatalytic behavior of the binary system ZnO/TiO2 incorporated into acrylic varnish in the degradation of non-purgeable organic carbon (NPOC) in samples of humic acids and fulvic acids + humins. Reactions were conducted under acidic, neutral, or alkaline conditions. NPOC degradation was low in fulvic acid + humin samples, regardless of photocatalyst concentration or pH. The proposed process resulted in high degradation of humic acids, especially under conditions of low chemical stability, which facilitated oxidation. A maximum humic acid degradation of 65% was achieved using high concentrations of TiO2 in acidic medium.